Lou Andreas-Salomé, une philosophe mystique du féminin - Ondine Arnould (Recherches Germaniques)
If Lou Andreas-Salomé is still mainly known for her relationships with Great Men, this article aims at exposing her own thinking by questioning her conceptual system built up through the different disciplines she practiced. Her conception is fundamentally embedded in a mystical psycho-philosophy of Life. This mysticism is rooted in a holistic monism. It places the feminine at its centre, because the feminine is considered as the privileged place of creation, of flesh as well as of mind. This article attempts to characterise this thinking, which is at the same time unitary and multiple, timeless and fundamentally dynamic. In this sense, we will analyse to what extent Lou Anderas-Salomé’s thinking can be qualified as philosophical as well as mystical.